Polarographic Study of Cerium(IV)-Antipyrine Complexes at DME in Various Water Samples - Giridhar, C.; Varaprasad, A.; Naidu*, N.V.S. (Asian Journal of Chemistry, 2013)
A catalytic polarographic method for the determination of microgram quantities of Ce(IV) is developed based on the catalytic currents of cerium(IV) in the presence of NH4Cl-NH4OH at pH 5.8 with antipyrine. Antipyrine produces catalytic current with Ce(IV) at peak potential -0.1 to -0.6 V vs. SCE. The procedure is applied for the estimation of Ce(IV) in various water samples. The method is simple, sensitive and free from interference of many metal ions.